Pediatric Acute Promyelocytic Leukemia Presenting to the Emergency Department as Refusal to Ambulate. (12th June 2018) - Schwartz, Kevin R.; Hanson, Jennifer M.; Friedmann, Alison M.
Abstract : A previously healthy 10-year-old girl presented to the emergency department (ED) with a headache and vomiting which resolved with oral NSAIDs. The patient returned two days later unable to ambulate with mental slowing and lower extremity bruising. Labs demonstrated marked leukocytosis, severe anemia and thrombocytopenia, and disseminated intravascular coagulation (DIC). Brain MRI showed multiple intracranial hemorrhages. A peripheral blood smear demonstrated blasts with many Auer rods. A diagnosis of acute promyelocytic leukemia (APL) was made and therapy including all-transretinoic acid (ATRA) was initiated. Neurologic status returned to baseline within 1 week in the pediatric intensive care unit.